Purification of clavulanic acid produced by Streptomyces clavuligerus via submerged fermentation using polyethylene glycol/cholinium chloride aqueous two-phase systems - Panas, Paweł [UNESP]; Lopes, Camila [UNESP]; Cerri, Marcel O. [UNESP]; Ventura, Sónia P.M.; Santos-Ebinuma, Valéria C. [UNESP]; Pereira, Jorge F.B. [UNESP] (Elsevier, 2017)
Clavulanic acid (CA) is an important pharmaceutical compound produced by batch fermentation of Streptomyces clavuligerus. Since, CA is chemically unstable, its downstream processing should be studied to develop more efficient and resolute techniques. Herein, the use of aqueous two-phase systems (ATPS) composed of cholinium chloride, [Ch]Cl, was proposed as a novel platform for the recovery and purification of CA. Thus, the stability of CA in presence of different [Ch]Cl concentrations was initially studied, and the high biocompatibility of this salt was demonstrated by the low CA degradation levels. Then, the partitioning of CA using two types of polymeric ATPS has been investigated. Two ATPS formed by the combination of [Ch]Cl and two polyethylene glycol (PEG) polymers, PEG 600 g mol−1 (PEG-600) and polyethylene glycol methyl ether 550 g mol−1 (PEG-500-OMe), were used to assess the influence of the PEG nature, in addition to the concentration of the phase forming agents on the CA partitioning. It has shown that CA is almost equally distributed between the two-phases in equilibrium (0.6 < KCA < 1.6). Nevertheless, the selective extraction of CA for the [Ch]Cl-rich or PEG-rich phase by the proper adjustment of ATPS composition was attained. In the search for higher extraction efficiencies [EE (%)] and partition coefficients (KCA), a second polymeric ATPS platform composed of PEG-600 and sodium polyacrylate 8000 g mol−1 (NaPA-8000), applying [Ch]Cl as adjuvant was tested. The main results suggest the recovery of CA towards the PEG-rich phase (KCA ≥ 5.6 ± 0.6 and EE ≥ 85.5± 1.4%). The higher migration levels of CA have mainly resulted from the electronegative repulsion of NaPA-8000 over CA molecules. The ATPS with best performance for the CA extraction were selected for the recovery of CA directly from fermented broth of Streptomyces clavuligerus. In this set of experiments, the highest values of CA recovery yield and purification factor (respectively, 64.91± 1.99% and 22.70 ± 0.87) were attained for the systems PEG-600/NaPA-8000 and PEG-600/[Ch]Cl, respectively.
Keywords: Aqueous two-phase systems; Cholinium chloride; Clavulanic acid; Polyethylene glycol; Streptomyces clavuligerus